Analisis Kenyamanan Termal Pada Ruang Produksi Gamelan Bali Di Desa Tihingan - Marcelo, Benrio; Priambadi, I Gusti Ngurah; Septiadi, Wayan Nata (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract In making this gamelan, it is still done in the traditional way, which is smelting and then casting and forging. The speed of gamelan production depends on the pressure, capacity and distribution of air flow so that it can influence workers to carry out production activities optimally. To overcome this problem, a research was conducted using the application of CFD (Computational Fluid Dynamic) to analyze the air flow and temperature distribution in the gamelan production room. The subject of this research i s Pemade Sutama`s gamelan production room in Klungkung, which has a room temperature of 25?. The data in this study were obtained through direct observation, measurement and documentation. . The results of this simulation are still quite high because the cooling of the production room is still carried out convectively which allows the circulation of temperature and air in the room is not good causing workers to feel uncomfortable with room temperatures ranging from 50-70?. Keywords: Gamelan Bars, Temperature, Thermal Comfort, Production Room